Sex Specification and Heterogeneity of Primordial Germ Cells in Mice. - Akihiko Sakashita; Yukiko Kawabata; Yuko Jincho; Shiun Tajima; Soichiro Kumamoto; Hisato Kobayashi; Yasuhisa Matsui; Tomohiro Kono (PLoS ONE, 2015)
In mice, primordial germ cells migrate into the genital ridges by embryonic day 13.5 (E13.5), where they are then subjected to a sex-specific fate with female and male primordial germ cells undergoing mitotic arrest and meiosis, respectively. However, the sex-specific basis of primordial germ cell differentiation is poorly understood. The aim of this study was to investigate the sex-specific features of mouse primordial germ cells. We performed RNA-sequencing (seq) of E13.5 female and male mouse primordial germ cells using next-generation sequencing. We identified 651 and 428 differentially expressed transcripts (>2-fold, P < 0.05) in female and male primordial germ cells, respectively. Of these, many transcription factors were identified. Gene ontology and network analysis revealed differing functions of the identified female- and male-specific genes that were associated with primordial germ cell acquisition of sex-specific properties required for differentiation into germ cells. Furthermore, DNA methylation and ChIP-seq analysis of histone modifications showed that hypomethylated gene promoter regions were bound with H3K4me3 and H3K27me3. Our global transcriptome data showed that in mice, primordial germ cells are decisively assigned to a sex-specific differentiation program by E13.5, which is necessary for the development of vital germ cells.